The flexibility in the employment contract, response to the economic crisis? Reference to the Peruvian and Spanish case - De La Rosa Bedriñana, Mariem Vicky (2016)
This research aims to explore, through an effort of synthesis, the evolution of the Reform of Labour on recruitment affairs in countries like Spain and Peru, which — in spite of remaining different socially, politically and economically — display in a similar way an evolution on the legal treatment of working relations in times of economic crisis. It explains the results of an adaptation of the contract of labour which brought as a new approach a massive deployment of the temporary recruitment policies to reduce the level of unemployment. However, what began as a provisional and temporary measure has become in what it is today: a contract on the permanent use of the management, leaving aside the contracting of indefinite period and with it many other social rights.